2016
DOI: 10.1080/02770903.2016.1236941
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral killer cells do not differentiate between asthma patients with or without fixed airway obstruction

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…Severe asthma and allergic bronchopulmonary aspergillosis (ABPA) are risk factors for development of CPA in a minority of our patients [ 11 ]. Consistent with our findings, a recent study has shown no significant difference in CD3, CD8, and CD56 expression in patients with asthma and healthy controls [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Severe asthma and allergic bronchopulmonary aspergillosis (ABPA) are risk factors for development of CPA in a minority of our patients [ 11 ]. Consistent with our findings, a recent study has shown no significant difference in CD3, CD8, and CD56 expression in patients with asthma and healthy controls [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…15 However, limited knowledge exists on OA and NK cells in adult humans and results seem to be contradictory. 3,34,35 In this study, NK cell characteristics of OA patients with different subtypes according to their phenotypic properties were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies examining the effect of innate immunity as a link between obesity and asthma exist in obese asthma animal models 15 . However, limited knowledge exists on OA and NK cells in adult humans and results seem to be contradictory 3,34,35 . In this study, NK cell characteristics of OA patients with different subtypes according to their phenotypic properties were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Tubby et al 27 reported that the number, receptor expression, mitogen-activated protein kinase (MAPK) signaling molecule expression, cytotoxic mediator expression and functional cytotoxicity of peripheral blood NK cells were not different between asthmatic patients with fixed airway obstruction and those without.…”
Section: Introductionmentioning
confidence: 99%